About floristic records of the Mangystau flora - Imanbayeva, A.A.; Duissenova, N.I.; Lukmanov, A.B.; Dosshchieva, G.Zh.; Gassanova, G.G. (Fundamental and Experimental Biology, 2023)
This article presents the geographical novelties of the Mangystau flora discovered during the botanical expedition in 2023. One of the oasis territories of the Mangistau desert is the mountainous and foothill strips of the mountainous Karatau. For the first time, three species of woody plants, Prunus spinosa L., Rosa iliensis Chrshan, Armeniaca vulgaris L. from the family Rosaceae Juss, were found in the gorges of Kogez, Akmysh, Samal of the Mountain Karatau in the valleys of streams and along the slopes of the mountains. Thickets of bushes Prunus spinosa L. and endemic species of South Kazakhstan Rosa iliensis Chrshan occupy an area from 100 to 200 m2, and there are several single specimens of a rare and endemic species with a decreasing range of Armeniaca vulgaris L several specimens. All species are in good condition, plants have a high vitality, and no signs of damage were noted. Prunus spinosa and Rosa iliensis also showed abundant flowering and fruiting.